A distant area university investigation on students' activity, learning outcomes, and responses using synchronous online reading - Nurhilaliah Nurhilaliah; Kisman Salija; Haruna Abubakar Haruna (Center for Humanities and Innovation Studies, 2023)
Using synchronous online reading in the first semester of English students at a distant area university, this study proposes to determine the students' activity, learning outcomes, and responses to reading comprehension. Researchers gathered numerical data for this study to give a thorough and objective depiction of student activity, learning outcomes, and student reactions to reading comprehension. In this study, seventeen English-speaking students from a rural institution in the Indonesian region of South Sulawesi took part and were selected purposively. In an organized environment, the researchers used structured observation techniques to document particular actions or events methodically. A reading test and questionnaire were also used in this study. The reading test evaluated participants' characteristics, skills, or levels of knowledge. A questionnaire is a set of organized questions asked participants to gather their responses through the Likert scale. This study found that using synchronous online reading in a university located in a distant area has a positive effect on experiences and technology use, and it can alter how subjects are taught, how learning is carried out, and the difficulties that lecturers must overcome. Therefore, when choosing online learning that is regarded to help the learning process in the classroom, a lecturer might consider the study's findings. Future research may assess synchronous, asynchronous, and even hybrid learning in some distant area universities using large samples and a more diverse participant population